The JAK/STAT Pathway in Skeletal Muscle Pathophysiology - Moresi, Viviana; Adamo, Sergio; Berghella, Libera (Frontiers in Physiology, 2019)
The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway is a key intracellular mediator of a variety of metabolically relevant hormones and cytokines, including the interleukin-6 (IL-6) family of cytokines. The JAK/STAT pathway transmits extracellular signals to the nucleus, leading to the transcription of genes involved in multiple pleiotropic biological activities. The JAK/STAT pathway has been reported to be required for the homeostasis of different tissues and organs, where it is required for normal homeostasis. Indeed, when deregulated, it promotes the initiation and progression of pathological conditions, including cancer, obesity, diabetes and other metabolic diseases. In skeletal muscle, activation of the JAK/STAT pathway by the IL-6 cytokines accounts for opposite effects: if on the one hand, it promotes muscle hypertrophy by increasing the proliferation of satellite cells, on the other hand, it also contributes to muscle wasting. Epigenetics, by DNA and histone methylation and histone acetylation mechanisms, also regulates the expression of IL-6, as well as that one of the key members of the JAK/STAT pathway. Thus, manipulation of the JAK/STAT signaling pathway by specific inhibitors and/or drugs that modulate epigenetics is a promising therapeutic intervention for the treatment of numerous diseases. We focus this review in discussing the emerging evidence of the JAK/STAT pathway function in striated muscle pathophysiology and its potential role as an effector of the cross-talk between skeletal muscle and other organs.